Al-Quran Learning Strategies Using Digital Iqro Against Dyslexic Pupils' Emotional Monitoring in Banten Provincial Primary Schools - Anizar, Anizar; Kway Eng Hock (Tinta Emas Publisher, 2025)
This study is to find out the Al-Quran learning strategy using digital Iqro on the emotional monitoring of dyslexic students in primary schools in Banten Province. This study uses a quasi-experimental study design using a quantitative approach, and 100 respondents were selected purposively. A set of questionnaires was used and analyzed using descriptive and inferential statistics with the SPSS program. The results of the descriptive study from the Al-Quran learning strategy, the Wafa 1 Iqro reading assessment, and the emotional monitoring of dyslexic students overall mean scores were higher for the digital group compared to the conventional group. The study also found that there was a significant difference in mean scores between the digital group and the conventional group with a p-value of 0.00 < α = 0.05 for Al-Quran learning (direct and indirect) and emotional monitoring, except for the Wafa 1 Iqro reading assessment with a p-value of 0.05, and the set significance level of α = 0.05 is the same. Then there was also a significant difference (p = 0.00 < 0.05) together for the Al-Quran learning strategies (direct and indirect) between the reading assessment of emotional monitoring based on groups (conventional and digital) in this study. Therefore, this study can contribute to the field of knowledge or theory for teachers, schools, and policymakers in education to realize education in the current era of Society 5.0.